Evaluation of apple pomace as a raw material for alternative applications in food industries - Gullon, Beatriz (Array, 2007)
In order to measure the potential of apple pomace as a raw material for manufacturing food-related products (such as lactic acid, fiber-rich concentrates and pectin), samples from cider industry were assayed for composition and enzymatic digestibility. Alcohol-soluble compounds (monosaccharides, oligosaccharides and malic acid) accounted for 32–45 mass percent of oven-dry pomace. Glucose and fructose were the major components of this fraction. The alcohol-insoluble fraction accounted for 55–68 mass percent of oven-dry pomace and was mainly made up of neutral detergent fiber (62–69 percent of the mass fraction) and pectin (16.2–19.7 percent of the mass fraction). The feedstock content of N, P and metal ions (K, Mg, Fe and Mn) was favourable for further manufacture of lactic acid fermentation media. Apple pomace showed a high susceptibility to enzymatic hydrolysis: in media with a cellulase loading of 8.5 FPU/g of apple pomace and a cellobiase loading of 5 IU/FPU, about 80 % of the total glucan was converted into glucose after 15 h. Considering the low enzyme charge, liquor to solid ratio employed, reaction time needed to achieve the maximal sugars concentration and N, P and metal ion (K, Mg, Fe and Mn) content of samples, it can be concluded that apple pomace is a promising raw material for lactic acid production